Hangman – A Voice-Over Game - Ayesha Anees Zaveri (Journal of Computing Technologies and Creative Content, 2025)
This initiative aims to make games that relax, improve cognition, and provide entertainment. Mobile gamers have made the gaming sector the top category. Gaming applications generally accompany new technologies, and this trend has increased tenfold in the past year. People try games first on modern platforms. The program aims to provide workers with a break after a long day. The unpredictable future challenges software engineering and development, especially in the growing game development business. This game features voice recognition and attractive graphics. It is a multi-level strategy game. Age-specific tiers are available. Video games are more than just programming. Factual information makes stuff enjoyable. The game's atmosphere, storyline, characters, gaming mechanics, and artwork must be evaluated alongside the program. The Hangman Voice Over advanced technology. This game can improve cognition in disabled people. This may help kids learn.